Analysis of Teachers' Difficulties in Implementing Physics Practicum in SMA Banda Aceh City - Musdar, Musdar; Saputri, Mawarni; Hamid, Abdul (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study examines the implementation of physics practicum in the context of Merdeka Curriculum in high schools in Banda Aceh City. Using a descriptive qualitative approach with a survey method, this study aims to identify the challenges and difficulties faced by teachers in implementing physics practicum. Data were collected through questionnaires and interviews with physics teachers selected using purposive sampling technique. The results showed that most teachers (83%) had prepared the practicum module well, but faced obstacles in terms of adequate laboratory facilities (63%) and laboratory staff support (57%). Time management is also a challenge with only 63% of teachers feeling that the time allocation is sufficient. Despite this, the level of student discipline and responsibility in the practicum was quite high (92%). This study recommends the need for a review of time allocation, standardisation of laboratory facilities, and teacher professional development that focuses on technology integration in physics practicum in accordance with the demands of the Merdeka Curriculum.